Developing Student’ Speaking and Listening Skills through Modern Technology - Shand, Shellma Deu; Pratama, Rizky Mirani Desi; Hastuti, Dwi Puji; Khairunas, Sayyid (English Education: Jurnal Tadris Bahasa Inggris, 2024)
Students must learn English to broaden their minds, develop skills, and improve their quality of life through employment opportunities. However, effective communication in English is hard to achieve.  Therefore, this research aims to investigate the use of modern technology, YouTube videos, and audio, using smartphones as a learning tool to increase students’ interest in improving their speaking and listening skills. This research uses a qualitative method with a descriptive approach by interviewing and conducting a pretest and post-test interview. This research investigated students at SMP Negeri 45 Jakarta. This school implements Kurikulum Merdeka, in which teachers must be more creative and active in delivering the material. The results after giving students the technologies showed that many students obtained improved scores after using this method, effectively increasing their interest in learning English